Education during the COVID-19 pandemic: Access, inclusion and psychosocial support: Leaving no child behind - Parker, Malaka; Alfaro, Pablo (My University, 2021)
This analysis of the impact of remote learning is based on new and existing sources of data. The research team carried out a literature review; collected information from ministries of education (MoEs) through a questionnaire; organised focus groups with school principals and teachers, representatives of civil society organisations and other stakeholders; and interviewed representatives of organisations including parent teacher associations and student councils. Information was gathered in order to evaluate the impacts of school closures on students, with a particular focus on the psychosocial dimensions of remote learning, access and barriers to education for children from vulnerable and marginalized groups. Information was gathered about the measures implemented by MoEs and schools, and the needs of students and their families. These activities were conducted from October to December 2020. The information was used to identify best practices, lessons learned and to shape recommendations on how to build resilience in the education system and a more inclusive and equitable post-pandemic education system. This study synthetizes the main results and conclusions of the research. Chapter I provides more information on the research methods and data collection. Chapter II analyses the impact of COVID-19 on primary and secondary education in the Caribbean, including the mitigation measures and the measures for school reopening. Chapter III focuses on mental health and psychosocial impacts and response measures. Chapter IV address the needs of students with disabilities, migrant and refugee students and indigenous children and young persons, including the educational impact of COVID-19 and policies for marginalized students. Chapter V summarizes the main conclusions and policy recommendations, drawing attention to opportunities for innovation.